IMPLEMENTATION OF THE FORMATION OF STUDENT CHARACTER VALUES THROUGH CHILD FRIENDLY SCHOOL EDUCATION FOR GRADE V SD NEGERI SURYODININGRATAN 3 YOGYAKARTA - Dewiyanti, Ulfa (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
ABSTRACT This study aims to determine the implementation formation of student character values through child friendly school education for class V SD Negeri Suryodiningratan 3 Yogyakarta. This type of study is a descriptive qualitative research. This study used a purposive sampling technique with a total of 6 students as informants in grade VA, VB, and VC. Data collection was done by interview, observation, and documentation. The data was analyzed through qualitative analysis and continued with checking the validity of the data using triangulation of sources, techniques, and time. The results of the study concluded that the implementation of the formation of student character values through child friendly school education for grade V SD Negeri Suryodiningratan 3 Yogyakarta, namely the existence of child friendly school education, students can get the fulfillment of their rights in obtaining safe, comfortable, and enjoyable learning without violence. In forming character education, routine habituation activities, teacher examples, learning processes, and advice given to students are needed. The formation of student character values is strongly influenced by parenting, education, and the surrounding environment. In this study there are 12 implementations of the formation of student character values formed at SD Negeri Suryodiningratan 3 Yogyakarta based on existing activities, namely the character of tolerance, religious, honest, disciplined, peaceloving, creative, friendly/communicative, caring for the environment, fond of reading, love the homeland, responsibility and social area.